(untitled) (Research, Society and Development, 2022)
Chickpea (Cicer arietinum L.) is the fifth most cultivated legume in the world, it has high nutritional value and multiple possibilities for human consumption. India is the largest producer and consumer, but it is not self-sufficient, imports are necessary and the opening of the Brazilian market is possible. Organominerals are fertilizers produced from mixtures of mineral and organic materials, can be obtained from the residues of agricultural or agro-industrial activity. The incorporation of organic residues generated by agricultural activities in its production, presents itself as an alternative of fertilization, and reuse of sugarcane bagasse in the search for new technologies that reduce environmental impacts. The objective of this work was to evaluate the use of an organomineral fertilizer, obtained from the biomass of sugarcane in the cultivation of chickpeas. The experiment was carried out in pots, in a greenhouse at the Institute of Agricultural Sciences at UFMG, Montes Claros - MG. The experimental design used was completely randomized (DIC), in a 2x3 factorial scheme with 4 replications, being the factors: 2 - with and without liming and 6 treatments - with potassium phosphate, organomineral and potassium phosphate plus biochar. Conclusion, there was no effect of liming on chickpea production. The highest values ​​of variables related to chickpea plant growth and dry matter production were obtained in treatments with organomineral fertilizer produced from sugarcane biochar.